Resolución alternativa de conflictos: Mediación en línea como protección a los derechos del consumidor electrónico (2017)
New ways of dealing with consumer relations, in order to promote, protect and regulate relationships derived from the use of electronic means or also known as electronic commerce, have been imposed on the law. Therefore, there are various regulations that serve as a model for countries that, like Colombia, are consolidating a legal system for consumer protection, which is why online mediation is an alternative to the solution of Conflicts arising from electronic commerce. Next, the progress of a research project that seeks to “analyze the normative foundations in Mercosur and CAN member countries that allow the acceptance of the framework regulation of online mediation as a mechanism for resolving disputes arising from electronic commerce Cross-border” (García, Reyes & Toro, 2014, p. 10).